Creating visualizations with Seaborn in Excel - Mount, George (O'Reilly Media, Inc., 2024)
This video series explores integrating Python with Excel, teaching data analysts how to automate tasks, enhance data analysis, and create powerful visualizations. It solves efficiency issues in Excel, equipping viewers with skills to streamline workflows and extend Excel's capabilities using Python.
Online resource; title from title details screen (O'Reilly, viewed June 18, 2024)
Keywords: Microsoft Excel (Computer file); Python (Computer program language); Electronic spreadsheets -- Computer programs; Business -- Computer programs; Python (Langage de programmation); Tableurs; Logiciels; Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet